A Low Power 3-Stage Voltage-Controlled Ring Oscillator in 0.18 µm CMOS Process for Active RFID Transponder - Jalil, J.; Reaz, M. B. I.; Ali, M. A. M.; Chang, T. G. (Elektronika ir Elektrotechnika, 2013)
This paper presents a 3-stage ring voltage-controlled oscillator (RVCO), designed for active Radio Frequency Identification (RFID) transponders. High frequency local oscillators designed for battery-powered transponders are always crucial concerns for chip designers, as those oscillators consume considerable amount of power. Thus, the primary goal of this research work is to design a low power VCO at 2.45 GHz in the ISM band. In addition, in order to reduce overall oscillator size, ring based architecture has been adopted with easy integration technique. For varying the oscillating frequency from 2.2 GHz to 2.85 GHz, PMOS transistors with fixed value capacitors are utilized. Providing 1.8 V supply, the oscillator dissipates 6.99 mW of power and exhibits phase noise of -112 dBc/Hz at 10 MHz offset. The proposed RVCO is designed in CEDEC 0.18 µm standard CMOS process using Mentor Graphics environment. DOI: http://dx.doi.org/10.5755/j01.eee.19.8.2524